That figures! a crash course in math - S Hammelef, Danielle (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2015)
Simplifies middle school math curriculum and offers examples and activities to show readers how the topics tie in to real life". --
Science
a gift from book africa
1 2 13 15
Keywords: Mathematics -- Study and teaching (Middle school); Mathematics -- Study and teaching (Middle school) -- Juvenile literature; Mathematics